Zeolitic imidazolate frameworks‐8 modified graphene as a green flame retardant for reducing the fire risk of epoxy resin. (23rd March 2018) - Xu, Baoling; Xu, Wenzong; Wang, Guisong; Liu, Lvcheng; Xu, Jie
Abstract : A novel hybrid material of ZIF‐8/RGO (zeolitic imidazolate frameworks‐8 loaded the surface of graphene) was synthesised by a simple method and characterized. Then, ZIF‐8/RGO was added into epoxy resin (EP), and the flame retardancy and smoke suppression of the EP composites were studied. Compared with pure EP, the peak heat release rate and the total heat release of the EP composites were reduced remarkably, and their LOI and UL94 vertical burning rating were also improved. In addition, their smoke production rate and total smoke production were decreased drastically. The improved flame retardancy and smoke suppression were mainly attributed to the physical barrier effect of graphene. Meanwhile, the metal oxide decomposed from ZIF‐8 could contribute to the production of char residue and enhance the compactness of the char layer.